Administrative Regulations: Concept, Features, Problems of a Legal Regulation - V. A. Lushnikova (Теоретическая и прикладная юриспруденция)
The article analyzes a variety of normative legal acts, which is relatively new for the Russian legal system — administrative regulations. Signs that distinguish administrative regulations from other departmental regulatory legal acts are identified. The main stages of the inclusion of administrative regulations in the Russian legal reality in the course of the ongoing administrative reform are analyzed and considered. The author’s definition of administrative regulations is given, revealing their most essential characteristics. The types of administrative regulations are considered, their general and special features are revealed. The study made it possible to identify, formulate and characterize the main problems associated with the application of administrative regulations and suggest possible ways to solve them.